The Causality between Corporate Governance Practice and Bank Performance: Empirical Evidence from Indonesia - Utama, Cynthia A.; Musa, Haidir (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2011)
The aim of this study is to examine the existence of causality between corporate governance practice and performance of commercial banks in Indonesia. We also investigate the influence of age, capital adequacy, and type of commercial banks on bank performance and examine the influence of the bank size, foreign ownership, and listing status on corporate governance practice. The result shows that corporate governance practice, bank size and capital adequacy ratio have positive influences on bank performance in Indonesia. However, bank performance does not influence corporate governance practice. This study also finds that regional banks have better performance than private banks. The results of the study support the Central Bankâs efforts to enhance CG practices in the banking sector, to strenghten banksâ capital base and its policy to encourage banks to merge to become larger.Â Â Â Â Â